Inequalities in Access to Diabetes Technologies in Children with Type 1 Diabetes: A Multicenter, Cross-sectional Study from Türkiye - Kağan Ege Karakuş; Sibel Sakarya; Ruken Yıldırım; Şervan Özalkak; Mehmet N. Özbek; Nurdan Yıldırım; Gülcan Delibağ; Beray S. Eklioğlu; Belma Haliloğlu; Murat Aydın; Heves Kırmızıbekmez; Tuğba Gökçe; et al. (JCRPE)
Objective: To determine inequalities in access to diabetes technologies and the effect of socioeconomic factors on families with children with type 1 diabetes. Methods: In this multicenter, cross-sectional study, parents of children with type 1 diabetes completed a questionnaire about household sociodemographic characteristics, latest hemoglobin A1c (HbA1c) values, continuous glucose monitoring (CGM) and insulin pump use of children, the education and working status of parents. These characteristics were compared between technology use (only-CGM, only-pump, CGM+pump, no technology use). Results: Among 882 families, only-CGM users, only-pump users, and CGM+pump users were compared with no technology users, adjusting for age, sex, region, education levels, number of working parents, and household income. Children living in the least developed region had lower odds of having only-CGM [odds ratio (OR)=0.20, 95% confidence interval (CI): 0.12-0.34, p<0.001] and having CGM+pump (OR=0.07, 95% CI: 0.03-0.22, p<0.001) compared with those living in the most developed region. Children with parents who had not finished high school had lower odds of having only-CGM (mothers: OR=0.36, 95% CI: 0.19-0.66, p=0.001; fathers: OR=0.32, 95% CI: 0.18-0.60, p<0.001) or both CGM+pump (mothers: OR=0.27, 95% CI: 0.11-0.64, p=0.003; fathers: OR=0.34, 95% CI: 0.15-0.79, p=0.012) rather than no-technology compared to children whose parents have a university degree. Every $840 increase in the household income increased the odds by 5% for having only-CGM (OR=1.05, 95% CI: 1.02-1.09, p<0.001) or CGM+pump (OR=1.05, 95% CI: 1.01-1.08, p<0.001). Conclusion: Socioeconomic factors, such as parental education, region of residence, and income were associated with inequality in access to technologies. The inequalities are more prominent in access to CGM.